1979
DOI: 10.1071/bru9790175
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomic revision of the Lichen genus Hypogymnia in Australasia.

Abstract: The Australian, New Zealand and Papua New Guinean representatives of Hypogymia are reviewed. Photographs, keys and descriptions are given for the 11 species and five varieties. Two new species are described, H. enteromorphoides and H. kosciuskoensis, as well as a new variety, H. subphysodes var. austerodioides and six new combinations are made, namely H. lugubris var. sublugubris, H. lugubris var. compactior, H. pulchrilobata, H. pul- verata, H. tubularis and H. turgidula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…Everniastrum (Hale ex Sipman) Divakar et al, but belongs to clade II of Bulbothrix. Within different clades of parmelioid lichens, terrestrial species have evolved that differ morphologically from their saxicolous or corticolous relatives, such as vagrant species in the genus Xanthoparmelia (Elix et al 1986;Hale 1990), and some of them have been placed in separate genera. However, phylogenetic analyses demonstrated that they actually are not separate isolated lineages.…”
Section: Resultsmentioning
confidence: 99%
“…Everniastrum (Hale ex Sipman) Divakar et al, but belongs to clade II of Bulbothrix. Within different clades of parmelioid lichens, terrestrial species have evolved that differ morphologically from their saxicolous or corticolous relatives, such as vagrant species in the genus Xanthoparmelia (Elix et al 1986;Hale 1990), and some of them have been placed in separate genera. However, phylogenetic analyses demonstrated that they actually are not separate isolated lineages.…”
Section: Resultsmentioning
confidence: 99%
“…30 lichenan in the cell walls. The genus was monographed by Elix et al (1986) from Australasia and by Hale (1990). Xanthoparmelia conspersa is the type species.…”
Section: Discussionmentioning
confidence: 99%
“…We estimated ancestral range probabilities using the R package ‘BioGeoBEARS’ (Matzke, ) based on the dated tree obtained in beast . Species distributions were obtained from selected literatures (Bitter, ; Elix, ; Lai, ; McCune, Divakar, & Upreti, ; McCune & Wang, ) and unpublished results of the first author. Elvebakk () and Miadlikowska et al.…”
Section: Methodsmentioning
confidence: 99%
“…The saxicolous genera Arctoparmelia and Brodoa contain a number of species with wide, often circumpolar distribution (Goward, 1986;Hale, 1986), the corticolous genus Pseudevernia includes temperate species mostly restricted to a continent and adjacent areas (Egan, 2016;Hale, 1968;Nash & Elix, 2002). In contrast, Hypogymnia has a cosmopolitan distribution, occurring in temperate regions of both the northern and southern Hemisphere (Elix, 1979;Elvebakk, 2011;McCune, 2002;McCune, Martin, & Wang, 2003). Hypogymnia also comprises species with restricted distributional ranges, such as western North America, eastern Asia, and the southern Hemisphere or Eurasia (Elix, 1979;Elix & James, 1982;Hawksworth, 1973;Lai, 1980;McCune & Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%